2017
DOI: 10.1101/158105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factor analysis of equine strongyle resistance to anthelmintics

Abstract: introduction that contributed to lower drug resistance risk by 1.75. Premises falling under this 36 typology also relied more on their veterinarians suggesting they play an important role in the 37 sustainability of anthelmintic usage. Similarly, drug resistance risk was halved in premises 38 with frequent pasture rotation and with stocking rate below five horses/ha. This is the first 39 empirical risk factor analysis for anthelmintic resistance in equids, whose findings should 40 guide the implementation of m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Worldwide reports of anthelmintic drug failures against nematodes of veterinary importance have accumulated 3 , threatening the sustainability of livestock farming in some areas. The same pattern applies in horses whereby widespread benzimidazole failure and intermediate pyrantel efficacy against cyathostomin populations have been reported [4][5][6] . These small strongyles locate in their host hindgut and are responsible for growth retardation in young animals 7,8 .…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Worldwide reports of anthelmintic drug failures against nematodes of veterinary importance have accumulated 3 , threatening the sustainability of livestock farming in some areas. The same pattern applies in horses whereby widespread benzimidazole failure and intermediate pyrantel efficacy against cyathostomin populations have been reported [4][5][6] . These small strongyles locate in their host hindgut and are responsible for growth retardation in young animals 7,8 .…”
Section: Introductionmentioning
confidence: 69%
“…Factors contributing most to the selection of drug-resistant cyathostomin populations in equids remain uncertain 4,5 . However, significant and heritable inter-individual variation in resistance to strongylid infection has been reported in both domestic 11,12 and wild horse populations 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Low shedding horses tend to shed consistently low number of cyathostomin eggs over time 34,35 and TST has been shown to reduce the need for anthelmintics and reduce the costs associated with parasite control. [36][37][38] A risk factor analysis based on FECRT data from 688 horses on 39 French horse farms and riding schools indicated that FEC-based treatment regimens combined with individual anthelmintic dosage and the enforcement of tighter biosecurity around horse introduction resulted in a significant reduction in risk of drug resistance (relative risk of 0.57). 39 Modelling studies (which assumed little or no resistance at the outset) highlight a number of environmental and treatment factors that significantly impact the speed of development of resistance in relation to TST approaches:…”
Section: Does Targeted Selective Treatment Slow the Spread Of Anthelm...mentioning
confidence: 99%
“…This shift in species importance was derived from independent scattered pieces of evidence in the field (Love and Duncan, 1991). It was also associated with the development of drug resistant cyathostomin populations across the world (Fischer et al, 2015; Nielsen et al, 2018; Sallé et al, 2017; Tzelos et al, 2017). Independent evidence of ivermectin resistant Parascaris spp.…”
Section: Introductionmentioning
confidence: 99%